AVALIAÇÃO PRODUTIVA DE PEREIRAS DAS CULTIVARES HOSUI E ROCHA SOB DIFERENTES ESPAÇAMENTOS EM SISTEMA ORGÂNICO - Hennerich, Juçara Elza (2014)
The objective of this study was to determine the influence of planting space in relation to vegetative growth, productivity and fruit quality of the pear tree of cv. Rocha and Hosui at different spacing and organic production systems in the region of Guarapuava - PR. The evaluations were performed in the experimental orchard of the Department of Agronomy at UNICENTRO in two cycles (2011/2012 and 2012/2013), the vegetative and productive development and physical and chemical characteristics of the fruits were evaluated. The orchard was established in 2009 with the cvs. Rocha and Hosui grafted on quince rootstock ` CP `. The tested spacing were: 1.0, 0.8, 0.6 and 0.4 m among plants with 3.5 m between rows, equivalent to planting densities of 2,857, 3,571, 4,762 and 7,143 plants ha?¹, respectively. The experimental design was in randomized blocks in a 4x2 with six replications, each consisting of four plants. The plants were in central leader with closed canopy, in cordon and drip irrigated. It was observed in 2011 higher rates of budding, 87.5% for cv. Rocha and 83.8% for cv. Hosui. In 2012 the highest rates were 75.9% for cv. Rocha and 73.3% for cv. Hosui. For these two years, the cv. Rocha showed higher accumulation of Degree Day, however in the second year in anticipation of phenological phases occurred for both cultivars. A greater vigor, considering the variables vertical projection of estimated leaf area, canopy volume and diameter of trunk and branches was observed for cv. Hosui. The cv. Rocha reduced the chlorophyll content with planting density, while the chlorophyll content did not vary for cv. Hosui with the spacing. Regarding productivity, the second cycle of review cv. Hosui produced higher number of fruits (26.3) per plant and higher average fruit weight (127.3 g) in greater spacing, with higher productivity at lower spacing (3506.88 kg ha?¹). The cv. Rocha had average number of fruits per plant reduced, with a mean weight of 91.1 g, and greater productivity at lower spacing (1195 kg ha?¹). For soluble solids cv. Hosui did not vary as a function of spacing with higher content than the cv. Rocha, which reduced the levels with the density of planting. In the second cycle, the pulp of fruits cv. Hosui showed less firmness for all spacing compared to cv. Rocha. Among spacing, no significant differences for any of the cultivars were observed. The cv. Hosui shows to be more suitable to crowding considering vegetative growth, fruit quality and productivity, however an evaluation of more productive cycles will be necessary for both cultivars.